Dari ladang ke sawah: Pengaruh irigasi bendungan Argoguruh terhadap adaptasi pertanian kolonis Trimurjo (1935-1942) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Trimurjo is part of the Sukadana Colonization in Lampung District which was opened in 1935 as the parent village to accommodate all residents from Gedong Dalam who were relocated through the population colonization program or transmigration by the colonial government and were known as colonizers. Before the arrival of the colonists, the Trimurjo area was still a wilderness that had not been intensively used for agricultural activities. Along with the arrival of the colonists, the Argoguruh Dam was built to support agriculture-based life. This study aims to analyze the influence of the Argoguruh Dam on changes in the agricultural patterns of the Trimurjo colonists in the period 1935-1942. The method used is a historical method with four stages: heuristic, source criticism, interpretation, and historiography. The results of the study show that the Argoguruh Dam has a significant role in the transformation of the agricultural patterns of the Trimurjo colonists. This change is divided into two periods, namely the dry land period (plantations and rice fields) and the wetland period (rice fields). This transformation has an impact on the use of agricultural tools, planting systems, and production products. In the wetland period, rice yields increased significantly compared to gogo rice on dry land, thanks to the development of an irrigation system sourced from the Argoguruh Dam.
Keywords: Agricultural Patterns; Argoguruh Dam; Colonization; Irrigation; Trimurjo